2017
DOI: 10.1590/1806-90882017000100007
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Matter Fractions Under Second-Rotation Eucalyptus Plantations in Eastern Rio Grande Do Sul

Abstract: -The aim of the present study was to evaluate the effect of eucalyptus plantations on total organic C (TOC) and total N (TN) stocks as well as the C and N in the fulvic acid (FA), humic acid (HA), humin (HU), light organic matter (LOM) and microbial biomass (MB) fractions in soils with different textures in the eastern part of the state of Rio Grande do Sul, Brazil. Soil samples were collected from the 0-10-cm, 10-20-cm, 20-40-cm, 40-60-cm and 60-100-cm soil layers in a completely randomized experimental desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…), livestock (forage and wood), agriculture (mentoring, substrate, etc. ), and in the environmental area (CO 2 sequestration) (Silva et al, 2010;Soares et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), livestock (forage and wood), agriculture (mentoring, substrate, etc. ), and in the environmental area (CO 2 sequestration) (Silva et al, 2010;Soares et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They generally promote less demanding species in regards to soil chemistry and physics, since they are less dependent on pesticides; they minimize the action of erosive agents; they require reduced soil preparation and a long cycle between planting-harvesting-planting; they have a high soil nutrient cycling potential throughout the cutting cycle by litter deposition (Pinto et al, 2016); their cultural practices are less intense and use fewer machines or devices while planting and cultivating; when properly managed, they have the potential to provide shelter for fauna, allowing the integrated promotion of natural resource production and conservation (Soares et al, 2017). The evaluation of alterations in soil caused by changes in land use and occupation can become an important parameter to evaluate the sustainability of newer approaches that meet human needs (Silva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In our 2R chronosequence, we found no change in soil C across age classes for the 2R to 60 cm. Other studies of soil with moderate fertility or loamy texture also found limited changes in soil C within the second rotation (Mendham et al 2003;Soares et al 2017). In comparison to sandier sites with a higher potential to gain carbon, the soils with higher clay and silt likely have more protected and stable C, or possibly are closer to becoming more C saturated (Six et al 2002).…”
Section: Discussionmentioning
confidence: 95%
“…These studies, however, are not discerning fastercycling carbon from persistent carbon. Soares et al (2017) does discuss a correlation of molecules associated with chemically stabilizing organic matter (humic acid, fluvic acid, and humin), but this does not account for the physical parameters (aggregate occlusion, pore space inhibiting the activity of microbes) nor the biological controls of microbial communities. With an apparent lack of change in total soil carbon, persistent soil C could be lost and replaced with new vulnerable inputs of labile C. Alternatively, if the persistent C was not being disturbed, there could have been a new dynamic equilibrium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation